Speed analysis in football players of five different age-groups - Dourado, A. C.; Stanganelli, L. C. R.; Frisselli, A.; Campos, F. A.; Souza, O. B. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Introduction One of the most important biomotor abilities required for playing modern football is speed. According to BOMPA (1994) speed requires three major elements: reaction time, frequency of movement per unit time and speed of travel over a given distance. These abilities are determinant for football performance and that is why the evaluation of the athletes speed is necessary and must be part of the battery of tests applied to this team sport. Maximum speed is not achieved instantly but rather after acceleration of at least 30 meters, and normally it is reached after the 40 meter mark (BOMPA, 1994). Thus, the objective of this study was to evaluate the speed of football players of five different categories and divided by age-groups using the 40 meter speed test as well as to compare the results obtained for this variable among the respective five age-groups. Methods The sample was composed of 121 football players of five different categories and divided into age-groups: Under 14 (Height 1,60 +/- 0,10 m; Weight 47,49 +/- 8,78 m), Under 16 (Height 1,71 +/- 0,09 m; Weight 59,12 +/- 8,59 m), Under 18 (Height 1,76 +/- 0,06 m; Weight 66,57 +/- 6,69 m), Under 20 (Height 1,79 +/- 0,07 m; Weight 71,91 +/- 7,65 m) and Professional (Height 1,78 +/- 0,06 m; Weight 73,57 +/- 5,72 m) categories. All these athletes belonged to the professional team Londrina Esporte Clube/Londrina Junior Team . Parana State, Brazil. During the regular season the athletes were submitted to the 40 meter speed test which was timed by a precision system of electronic photocells (real time (s) and distance (meters/second). The data were collected every 10 meters of the running test. For the comparison of the means, it was used the descriptive statistics as well as the ANOVA-MANOVA analysis. When necessary the Post Hoc was applied utilizing the Scheffe test. The significance level was set at p . 0,05. Results The results showed that only the age-groups Under 14 and Professional presented means that were statistically significant in all distances of the test. The age-group that performed the best was the Under 20 which demonstrated greater acceleration and speed throughout the test. Also, it was possible to verify that the speed increased progressively according to the age-groups as demonstrated on TABLE 1. Discussion/Conclusion According to these results, it was possible to conclude that the evaluation of speed for the five categories is a very important tool to better understand the behavior of this variable according to the process of growth and development in such a special population, considering that it could be influenced by many aspects such as training intensity and volume, maturation status of the athletes and others. Also, knowing the characteristics of each age-group allows a better monitoring of the athletes performance during a regular season and the provision of better conditions to prescribe the training loads more adequately.